To solve this system of equations using elimination, we will need to eliminate one of the variables by adding or subtracting the two equations.
Given equations:
1) 3x + 6y = 18
2) 3x + y = -7
To eliminate the x variable, we can subtract equation 2 from equation 1:
(3x + 6y) - (3x + y) = 18 - (-7)
5y = 25
y = 25/5
y = 5
Now that we have found the value of y, we can substitute it back into one of the original equations to solve for x. Let's use equation 2:
3x + y = -7
3x + 5 = -7
3x = -7 - 5
3x = -12
x = -12/3
x = -4
Therefore, the solution to the system of equations is x = -4 and y = 5.
Solve this system of equations using elimination (show your work)
3x+6y=18
3x+y=-7
1 answer